Job based curriculum development / Shaira Ismail and Norhaslinda Hassan - Ismail, Shaira; Hassan, Norhaslinda (Universiti Teknologi MARA, Pulau Pinang, 2022)
An effective and comprehensive curriculum should reflect the philosophy, aims, objectives, learning experiences, instructional resources, and assessments that are aligned with the government education philosophy and, most significantly, fit the job or position needs in the industries. To construct the job-based curriculum model, an examination of the job specification (JS) and job description (JD) from job advertisements are crucial to analyze the skills, knowledge, talents, and other competencies required by the industries or employers. Higher education institutions (HEIs) should determine the skills, knowledge, abilities and other attributes (SKAOs) that are necessary for various professions and industries to ensure that the curriculum is dependable and up to date in order to increase the graduate marketability index. It is to ensure that graduates are prepared for the workforce. The employability skills, knowledge, abilities and competencies should be firmly entrenched in the curriculum. These are often outlined in the JD and JS as a result of the job analysis (JA).